A dual risk model with additive and proportional gains: ruin probability and dividends. (8th June 2023) - Boxma, Onno; Frostig, Esther; Palmowski, Zbigniew
Abstract: We consider a dual risk model with constant expense rate and i.i.d. exponentially distributed gains $C_i$ ( $i=1, 2, …$ ) that arrive according to a renewal process with general interarrival times. We add to this classical dual risk model the proportional gain feature; that is, if the surplus process just before the i th arrival is at level u, then for $a>0$ the capital jumps up to the level $(1+a)u+C_i$ . The ruin probability and the distribution of the time to ruin are determined. We furthermore identify the value of discounted cumulative dividend payments, for the case of a Poisson arrival process of proportional gains. In the dividend calculations, we also consider a random perturbation of our basic risk process modeled by an independent Brownian motion with drift.